Analyzing the Role Quality Of Life on the Kind and Extent of Political Participation (Case Study: Isfahan City) - nejat mohammadifar; hossein masoudnia; amirmasoud shahramnia; abbas hatami (توسعه اجتماعی)
This article aims role quality of life on the kind and extent of political participation is written. Methodology of the paper is based on descriptive-survey, and through questionnaire data has been collected. Data obtained from different parts of the Isfahan city and then through a questionnaire completed by 385 individuals analyzed by using spss software is located. Findings of this research indicate the existence of a significant correlation among variables Personal well-being (r=0.15), Family well-being (r=0.19), Satisfaction of Interpersonal relations (r=0.28), Economic situation (r=0.15) and Social justice (r=0.28) as well as Parochial political participation. Also the existence of a significant correlation among job well-being variables (r=0.17), satisfaction of interpersonal relations (r=0.18), economic situation (r=0.19) and social justice (r=0.43), as well as subject political participation. The existence of a significant correlation among satisfaction of municipal services variables (r=0.25), family well-being (r=0.19), satisfaction of interpersonal relations (r=0.27) and social justice (r=0.24), as well as civil political participation. Also Findings of this research indicate the existence of a significant correlation among Quality of Life and Political Participation (r=0.41), generally. Findings of research indicate the existence of a significant correlation among Quality of Life and level of Political Participation, generally.